Ballad and its Connection to the Myth - Velaj, Olimbi (Richtmann Publishing, 2012)
Ballads are defined as a literary genre in Albanian studies, thus their connection with music seems rather vague. In this treatwe will show a typological subdivision of the ballad in Albanian culture and its connection with the myth. More specifically, thisconnection is seen in the ballad of walling up wife. The motif of the sacrifice in construction, as opposed to that of the dead brother orthat of the husband coming home, is unknown to the other part of Europe folklore. On the other hand, the rite of the sacrifice inconstruction has been and continues to be widely known in many countries all over the world. In this study we try to clear the presenceof the walled up wife motif in Balkan and Albania and also the situation of this motif’s blending in the fund of the ballads.